Penerapan Metode MAUT Dalam Penentuan Kelayakan TKI dengan Pembobotan ROC - Dimas Hadityo Ramadan; M Ridho Siregar; Saidi Ramadan Siregar (STMIK Budi Darma, 2022)
-Indonesia is a country that has a large population, but the employment opportunities are not sufficient in increasing the survival of the population. This has caused many Indonesians to become Indonesian Migrant Workers (TKI) abroad. During this period of time in making a decision on the eligibility of TKI abroad at the stage of selecting prospective TKI at BP3KI, it is only done by looking at the criteria for work experience, whereas at the selection stage for TKI candidates can use several criteria, namely education, work experience, age, knowledge, skills, and ethics. In determining the eligibility of Indonesian migrant workers abroad, a decision support system is needed. The method applied in this study is the MAUT method with ROC weighting. The application of these two methods is expected to be able to produce alternatives from a number of existing alternatives, while the best alternative result from this research is Alternative A5